1999
DOI: 10.1002/(sici)1097-4628(19990906)73:10<1823::aid-app1>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Blends of polycarbonate and polysulphone-polydimethyl-siloxane block copolymers: analysis of compatibility and impact strength

Abstract: ABSTRACT:The possibility of modifying polycarbonates by using dian (Bisphenol A) polysulphone-polydimethyl siloxane block copolymers having multiblock structure and triblocks with end polydimethyl siloxane or a polysulphone block structure was shown. In triblock copolymers the polydimethyl siloxane blocks have a constant molecular weight equal to 2500, while in polyblocks it was assumed to be 2500 and 10,000. The molecular weight of polysulphone blocks varied between 700 and 9000 in triblocks or between 500 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…The analysis of temperature dependences of mechanical loss tangent (tanδ) and dynamic shear modulus (G′) of the samples gave information on the dynamic-mechanical (relaxation) properties of the materials. The tests were run as in other works [2,20], using the reverse torsion pendulum of design developed at MPRI NAS, Belarus. The test frequency was 1 Hz.…”
Section: Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of temperature dependences of mechanical loss tangent (tanδ) and dynamic shear modulus (G′) of the samples gave information on the dynamic-mechanical (relaxation) properties of the materials. The tests were run as in other works [2,20], using the reverse torsion pendulum of design developed at MPRI NAS, Belarus. The test frequency was 1 Hz.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Relaxation spectrometry allows estimating variations in dynamic mechanical properties of blends within a wide temperature range and yields experimental data which can be indicative of specific interactions between phases in blends [2,20,21]. The temperature dependences of tanδ and G′ for initial PET and PC, as well as blend compositions based on them, are shown in Table 1 values of the parameters that characterize relaxation properties of the materials are listed in Table 3.…”
Section: Dynamic-mechanical Properties Of the Blendsmentioning
confidence: 99%
“…In response to this problem, the use of silicone derivatives as flame retardants is researched because of their high heat resistance and nontoxicity during combustion 8. Previous researches using silicone derivatives as flame retardants include investigations of polymethylphenylsilsesquioxane (PMPSQ) and polydimethylsiloxanes mixed with PC, PS, PMMA, and other plastics 9–12. Recent studies on POSS have been reported indicating reinforced mechanical and thermal properties of blends of silicone derivatives and PC,13, 14 rarely there is systematical study on the influence of the PMPSQ contents on the comprehensive properties of PC.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on the impact toughening of PC by blending it with other polymers. Many of these studies have focused on rubber blends 3–7. It has been shown that the addition of a small amount of acrylonitrile‐butadiene‐styrene (ABS) and core‐shell rubbers to PC can improve impact strength.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have focused on rubber blends. [3][4][5][6][7] It has been shown that the addition of a small amount of acrylonitrile-butadiene-styrene (ABS) and core-shell rubbers to PC can improve impact strength.…”
Section: Introductionmentioning
confidence: 99%